Beliefs about teaching and learning in university teachers: Revision of some studies - Solis, Carmen A. (2015)
Research shows that the belief the teachers have about teaching, learning, and their students affect their planning, instructing and evaluation processes in the classroom, and also that they have a repercussion on the student’s learning and performance in the classroom. In the case of university teachers, the beliefs about the teaching-learning process are shaped from the experience their own school and university teachers had. This leads them to repeat the same teaching schemes their old teachers had, thus perpetuating traditional pedagogical practices. For this reason, higher education teachers’ beliefs are becoming a more and more relevant research subject in several countries. To know the teachers’ belief scheme regarding the teaching-learning process will allow to generate teaching reflection processes about their pedagogical practice, their relation to change and their improvement.